Sosialisasi Fungsi Buraketto Pada Konstruksi Jembatan Bagi Siswa SMA di Oogi, Kota Taketa, Prefektur Ooita, Jepang - Al’jufri, Muhammad Bagir; Hariyadi, Hariyadi; Hartana, Hartana (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The construction of infrastructure in the form of a bridge carried out by a Japanese company, Takayama Gumi, aims to increase the strength of bridge infrastructure and provide regional connectivity. The installation process for bridge construction ensures the strength and durability of the structure during an earthquake. In the development process, socialization involved various parties, such as the government and educational institutions, to provide an understanding of the importance of bracket technology, known well in Japan as Buraketto, in bridge construction. The socialization aims to increase awareness of the importance of Buraketto technology as earthquake resistance, explain the positive impacts of its use, and improve occupational safety. This socialization was done through presentations and field surveys, where the students were allowed to see firsthand the process of installing Buraketto. As a result, students' comprehensive understanding of Buraketto as an earthquake-resistant technology increases, and students gain more enthusiasm for studying civil engineering as a career option in the future.